Classroom Resource Optimization of the English Four-Step Model Based on Deep Learning - Min Zhao (Hindawi-Wiley, 2021)
The existing LBL (lecture-based learning) and CBL (case-based learning) teaching modes of English majors in colleges and universities do not contribute to cultivating students’ inquisitive thinking and independent learning ability, whereas the problem-centered PBL (problem-based learning) teaching mode can precisely make up for these shortcomings. This study firstly constructed a PBL “four-step” teaching mode and then realized the innovative application of PBL teaching model in the teaching of English majors in new universities. Then, we designed a method of English classroom resource optimization based on IMOCS-BP neural network, and then, the classroom resource optimization reconstructs the teaching process with unique connotation essence. The experiments show that the BL “four-step” teaching model is designed to achieve the four key elements of “flexible English learning environment, transformed learning the culture, customized content and professional educators”; the designed neural network has optimized the English classroom resources.